Collaborative Outcomes study on Health and Functioning during Infection Times (COH-FIT): global and risk-group stratified course of well-being and mental health during the COVID-19 pandemic in adolescents - Solmi, Marco; Meyer-Lindenberg, Andreas (Journal of the American Academy of Child and Adolescent Psychiatry, 2025)
Objective - To identify the COVID-19 pandemic impact on well-being/mental health, coping strategies, and risk factors in adolescents worldwide. - Method - This study was based on an anonymous online multi-national/multi-language survey in the general population (representative/weighted non-representative samples, 14-17 years of age), measuring change in well-being (World Health Organization-Five Well-Being Index [WHO-5]/range = 0-100) and psychopathology (validated composite P-score/range = 0-100), WHO-5 <50 and <29, pre- vs during COVID-19 pandemic (April 26, 2020-June 26, 2022). Coping strategies and 9 a priori- defined individual/cumulative risk factors were measured. A χ2, penalized cubic splines, linear regression, and correlation analyses were conducted. - Results - Analyzing 8,115 of 8,762 initiated surveys (representative = 75.1%), the pre-pandemic WHO-5 and P-score remained stable during the study (excluding relevant recall bias/drift), but worsened during the pandemic by 5.55 ± 17.13 (SD) and 6.74 ± 16.06 points, respectively (effect size d = 0.27 and d = 0.28). The proportion of adolescents with WHO-5 scores suggesting depression screening (<50) and major depression (<29) increased from 9% to 17% and 2% to 6%. WHO-5 worsened (descending magnitude, with cumulative effect) in adolescents with a mental or physical disorder, female gender, and with school closure. Results were similar for the P-score, with the exception of school closure (not significant) and living in a low-income country, as well as not living in a large city (significant). Changes were significantly but minimally related to COVID-19 deaths/restrictions, returning to near-pre-pandemic values after >2 years. The 3 most subjectively effective coping strategies were Internet use, exercise/walking, and social contacts. - Conclusion - Overall, well-being/mental health worsened (small effect sizes) during the early stages of the COVID-19 pandemic, especially in vulnerable subpopulations. Identified at-risk groups, association with pandemic-related measures, and coping strategies can inform individual behaviors and global public health strategies. - Plain language summary - The impact of COVID-19 and related restrictions on the mental health of children and adolescents remains unclear. This study conducted an anonymous online survey with over 8,100 adolescents aged 14 to 17 years worldwide. Results showed a significant decline in wellbeing, with depression rates increasing from 9% to 17% returning to near- pre-pandemic values after about 2 years. Adolescents with preexisting mental health conditions, female youth, and those affected by school closures were particularly vulnerable. Effective coping strategies included internet use, exercise, and social contacts, highlighting areas for public health focus to support youth during pandemics. - Study preregistration information - Physical and mental health impact of COVID-19 on children, adolescents, and their families: The Collaborative Outcomes study on Health and Functioning during Infection Times - Children and Adolescents (COH-FIT-C&A); https://doi.org/10.1016/j.jad.2021.09.090 - Diversity & Inclusion Statement - We worked to ensure sex and gender balance in the recruitment of human participants. We worked to ensure race, ethnic, and/or other types of diversity in the recruitment of human participants. We worked to ensure that the study questionnaires were prepared in an inclusive way. The author list of this paper includes contributors from the location and/or community where the research was conducted who participated in the data collection, design, analysis, and/or interpretation of the work. We actively worked to promote inclusion of historically underrepresented racial and/or ethnic groups in science in our author group. We actively worked to promote sex and gender balance in our author group. One or more of the authors of this paper self-identifies as a member of one or more historically underrepresented racial and/or ethnic groups in science.